Moulin density controls drainage development beneath the Greenland ice sheet. Issue 12 (2nd December 2016) - Banwell, Alison; Hewitt, Ian; Willis, Ian; Arnold, Neil
Abstract: Uncertainty remains about how the surface hydrology of the Greenland ice sheet influences its subglacial drainage system, affecting basal water pressures and ice velocities, particularly over intraseasonal and interseasonal timescales. Here we apply a high spatial (200 m) and temporal (1 h) resolution subglacial hydrological model to a marginal (extending ~25 km inland), land‐terminating, ~200 km 2 domain in the Paakitsoq region, West Greenland. The model is based on that by Hewitt (2013) but adapted for use with both real topographic boundary conditions and calibrated modeled water inputs. The inputs consist of moulin hydrographs, calculated by a surface routing and lake‐filling/draining model, which is forced with distributed runoff from a surface energy‐balance model. Results suggest that the areal density of lake‐bottom moulins and their timing of opening during the melt season strongly affects subglacial drainage system development. A higher moulin density causes an earlier onset of subglacial channelization (i.e., water transport through channels rather than the distributed sheet), which becomes relatively widespread across the bed, whereas a lower moulin density results in a later onset of channelization that becomes less widespread across the bed. In turn, moulin density has a strong control on spatial and temporal variations in subglacial water pressures, which will influence basal sliding rates, and thus ice motion. The density of active surface‐to‐bed connections should be considered alongside surface melt intensity and extent in future predictions of the ice sheet's dynamics. Key Points: Combining models of supraglacial and subglacial drainage is an effective way of assessing the impact of moulin density on subglacial drainage A higher moulin density causes an earlier onset of subglacial channelization and results in a more widespread channel network across the bed Moulin density has complex and contrasting effects on water pressure in the early and late melt season, with basal sliding implications